O monitoramento metacognitivo em tarefas que envolvem a criatividade verbal - Deffendi, Luma Tiziotto (Universidade Federal de São Carlos, 2015)
Metacognition involves the knowledge that individuals have with respect to their own cognitive processes, and includes self- monitoring, self-regulation and evaluation of their cognitive activities. This study focuses on the evaluation of metacognitive monitoring via the solicitation of judgements, which can be used as a tool for the assessment of metacognition. From a cognitistic perspective, creativity is the term used to refer to a set of processes that enable variations in concepts, in order to facilitate the development of new ways of grouping ideas. The present study aimed to investigate metacognitive monitoring among university students when performing tasks that involve verbal creative processes. Participants included 82 university students, of both genders, who completed the Torrance’s Verbal Test of Creative Thinking. After finishing the creativity test, they were asked to evaluate their performance (metacognitive monitoring). The Results suggest that the participants appear to have poor metacognitive monitoring skills in tasks involving creativity, since the correlation between actual and estimated performance was weak. Future researches on this subject should address new hypotheses and work to eliminate possible methodological bias in the present study resulting from, for example, the homogeneity of the sample and limitations of the Creativity Monitoring Scale.
Keywords: Metacognition; Monitoring; Verbal creativity; College Students; Metacognição; Monitoramento; Criatividade Verbal; Estudantes Universitários; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA